MATERIAL INVENTORY INFORMATION SYSTEM AT UD. ALAM RAYA WEB-BASED USING THE WATERFALL METHOD - Yudi Mulyanto; Eri Sasmita Susanto; Arsyah Kumalasari (Computer Science Department, Malang National Institute of Technology, 2024)
UD. Alam Raya is a trading business engaged in the sale of building materials. UD. Alam Raya provides various types of building materials such as wood, nails, cement, iron, electrical tools, pipes, glue, and other building materials. In processing inventory and finances are still not computerized. Recording of sales transactions and purchases of goods is still done manually on notes and large sheets of paper grouped by transaction date. Recording on paper media is less effective because when the paper is exposed to water, the writing on it also fades, hindering the process of making financial reports. Based on these problems, a computerized building material inventory information system is needed in order to facilitate sales and purchase data processing as well as financial reports at UD. universe. This study uses qualitative research methods and the waterfall software development method, as well as the PHP (Hypertext Preprocessor) programming language using the CodeIgniter framework. This research succeeded in designing and creating a building material inventory information system at UD. universe. The benefit of this building material inventory information system is that it makes it easier to make purchase reports, sales reports, and financial reports at UD. universe